Core Functional Requirements for Fiscal Management Systems - Hashim, Ali (IMF Working Papers; Working Paper, 1994)
This paper presents a framework for planning the development of computerized government budgeting and accounting systems in economies in transition and developing economies. It argues that a comprehensive framework is needed to enable fiscal management issues to be addressed effectively, then outlines a methodology for planning systems development and proposes strategies for implementing the methodology in transitional and developing economies.